Pengaruh CRM (Costumer Relationship Management) Terhadap Keunggulan Bersaing Pada Distro 88 Pekanbaru - Annisa Mardatillah (SYNERGY: Jurnal Bisnis dan Manajemen, 2023)
This study determines and analyzes CRM (Customer relationship management) on competitive advantage in Distro 88 Pekanbaru. The indicators of CRM (customer relationship management) used are people, processes, and technology. This research is located in Distro 88 Pekanbaru using a descriptive research type that prioritizes questionnaires to collect data and empirical conditions from the research location. The method used is quantitative. The population in this research is Distro 88 Pekanbaru visitors. The sample of this research is 100 people. The sampling technique used is incidental sampling. Types and data collection techniques comprised primary data from observation, questionnaires and interviews. Based on the results of the data analysis technique used is descriptive analysis. The results of this study indicate that CRM (customer relationship management) significantly affects competitive advantage at Distro 88 Pekanbaru.